Plant-based food: study consumer choice criteria (Research, Society and Development, 2020)
Growing demand for plant-based food is already a reality in the global food market. These foods serve groups of heterogeneous profile. However, far too little is known about the factors that influence their choice. Thus, the aim of this paper was to investigate the criteria involved in choosing plan-based foods from consumers in Fortaleza-CE and the metropolitan region. A market research was developed using a structured questionnaire inspired by the Food Choice Questionnaire, obtained in person, in a university cafeteria and a vegetarian restaurant, and online. The respondents were mostly composed of people between 18 and 35 years old, female and consumers of vegetable products daily. The questionnaire revealed metric property, with α values between 0.664 and 0.804. The criteria most important for the food choice to the respondents were “price” (6.12 ± 1.24) and “sensory appeal” (6.03±1.34). When comparing the consumer segments, the “weight control” criterion was more relevance for women. From the observations and analyzes made it, this research presents important information for the development of plant-based product market in the food industry with the criteria considered to be most relevant for their consumption.